Aerobic radical multifunctionalization of alkenes using tert-butyl nitrite and water - Hirose, Daisuke; Taniguchi, Tsuyoshi (Beilstein Journal of Organic Chemistry, 2013)
Water induces a change in the product of radical multifunctionalization reactions of aliphatic alkenes involving an sp3 C–H functionalization by an 1,5-hydrogen shift using tert-butyl nitrite and molecular oxygen. The reaction without water, reported previously, gives nitrated γ-lactols, whereas the reaction in the presence of water produces 4-hydroxy-5-nitropentyl nitrate or 4-hydroxy-3-nitropentyl nitrate derivatives.
Keywords: C−H oxidation; free radical; nitration; oxygen; radicals; water